PNEUMONIA IN CHILDREN: OLD CHALLENGES AND NEW OPPORTUNITIES - S.A. Tsar'kova; P.V. Kuznetsov; N.G. Kupreeva (Union of pediatricians of Russia, 2011)
Influenza and other ARVIs in children are frequently complicated by pneumonia, which significantly exacerbates the diseases prognosis. At a flu children younger 5 years and children with related health conditions are at the highest risk of severe pneumonia. In the WHO's opinion, the best way of preventing, among others, pneumococcal infection, is vaccination. The article presents the groups of children most susceptible to pneumococcal infection, identifies the optimum vaccination timing, as well as vaccines that are used to prevent this infection.Key words: influenza, ARVI, pneumococcal infection, pneumonia, vaccination, children.